An efficiency study of a pivot-based algorithm for similarity search on a heterogeneous platform - Uribe-Paredes, Roberto; Arias, E.; Cazorla, D.; Sanchez, J. L. (My University, 2017)
Graphics processing units have definitely consolidated a position of privilege in the acceleration of general purpose applications. Search algorithms in large databases are a clear example of applications that benefit from computing platforms based on these devices. To obtain an efficient implementation of a given code using these platforms, it is very important to take into account their features. However, the characteristics of the application and certain overheads still introduced by these platforms, make it not always advisable to use these devices to obtain significant time reductions. In this paper, we show how different properties of current graphics processing units are exploited for improving a version of the general metric structure similarity search algorithm introduced by the authors, and compare it with a multithreaded version of the same algorithm using conventional processors. The analysis of the results provides us relevant data to determine the most appropriate computing platform.
Keywords: similarity search; metric spaces; gpu-based platforms; optimization